PENDAMPINGAN APLIKASI PENGAWET NIRA ALAMI TANGKIS PADA PENGRAJIN GULA KELAPA DI DESA JLADRI KECAMATAN BUAYAN, KABUPATEN KEBUMEN - Karseno Karseno; Tri Yanto; Mujiono Mujiono (Dinamika Journal : Pengabdian Masyarakat, 2021)
Jladri Village in Buayan District, Kebumen Regency is one of the coconut sugar producing areas. The problem faced by coconut sugar crafters is that the sap is easily damaged due to microbial contamination. To prevent damage to the sap, the sugar craftsmen add a natural or synthetic preservative (sodium metabisulfite). There are still many coconut sugar craftsmen in this village who use synthetic preservatives to control the damage of sap. Crafters tend to use synthetic preservatives in doses that exceed food safety regulatory standards so that it has an impact on the quality and safety of the coconut sugar produced. To replace synthetic sap preservatives, the application of science and technology program (Penerapan IPTEKS) activities are carried out assisting the use of natural based sap preservatives, namely TANGKIS. The activity was carried out through the stages of socialization, training, making demonstration plots, and providing ongoing assistance in the use of the TANGKIS natural preservative. The results showed that farmers received and applied the TANGKIS sap preservative. The use of TANGKIS produces better quality coconut sugar than coconut sugar which uses synthetic sap preservatives.